Parenting of Pre-Prosperous Families on The Independence of Children with Slow Learner - Martaningrum, Alit; Prastiti, Wiwien Dinar; Lestari, Sri (Universitas Negeri Surabaya, 2024)
Background: The limitations of children with slow learner (CwSL) make them dependent on other people so that they can be improved through education at school and parenting at home. Parenting is influenced by economic conditions, including in Pre-Prosperous Families (PPS). Objective: To explore and describe parenting in PPS on the independence of CwSL. Method: Qualitative with a focus on case studies with data collection in the form of interviews, observations and documentation. The research subjects were two pairs of parents of MRC in PPS with the extended family analysis unit. The data analysis is pattern matching, explanation and time series analysis. Transferability test with data triangulation. Results: Not all parents know the obstacles and parenting methods for MRC due to busy work and lack of knowledge due to low educational background. A child's obstacles and needs can be detected from the teacher's recommendations for further examination. Conclusion: Children's social independence appears to better involve grandmothers when parents work. However, children's social development can also improve when parents receive therapy from PLDPI.AbstrakLatar Belakang: Keterbatasan anak lamban belajar (CwSL) membuat mereka bergantung pada orang lain sehingga dapat ditingkatkan kemampuannya melalui pendidikan di sekolah dan pola asuh orang tua di rumah. Pola asuh orang tua dipengaruhi oleh kondisi perekonomian, termasuk pada Keluarga Pra Sejahtera (PPS). Tujuan: Untuk mengetahui dan mendeskripsikan pola asuh di PPS tentang kemandirian CwSL. Metode: Kualitatif dengan fokus studi kasus dengan pengumpulan data berupa wawancara, observasi dan dokumentasi. Subyek penelitian adalah dua pasang orang tua MRC di PPS dengan unit analisis keluarga besar. Analisis data yang dilakukan adalah pencocokan pola, penjelasan dan analisis deret waktu. Uji transferabilitas dengan triangulasi data. Hasil: Tidak semua orang tua mengetahui kendala dan metode pengasuhan MRC karena kesibukan pekerjaan dan kurangnya pengetahuan akibat rendahnya latar belakang pendidikan. Kendala dan kebutuhan seorang anak dapat diketahui dari rekomendasi guru untuk dilakukan pemeriksaan lebih lanjut. Kesimpulan: Kemandirian sosial anak nampaknya lebih melibatkan nenek ketika orang tua bekerja. Namun perkembangan sosial anak juga bisa meningkat ketika orang tua mendapat terapi dari PLDPI.